Youth Voice and Participatory Arts in Global Development - Group, The May (Routledge Explorations in Development Studies, 2025)
Youth Voice and Participatory Arts in Global Development looks at how arts-based methods can promote youth voice and engagement in global development. This book argues that engaging young people’s diverse voices, ideas and knowledges in matters that affect them is vital in enabling young people to become – and be recognised as – active citizens, developing more inclusive societies and ensuring that development programmes remain accountable to the young people they aim to benefit. We draw on youth-led participatory research projects from across Africa, Asia, Europe and Latin America, which used a range of art forms and engagement mechanisms, including participatory filmmaking, street art and the intersection of formal and non-formal education. Through this process, we develop the conceptualisation of transrational voice for epistemic justice and demonstrate the unique role that arts-based methods play in enabling this broad conceptualisation of voice that accounts for the multiple dimensions of young people's knowledges and experiences. This book will be of interest to researchers within international development, arts and youth studies, as well as to development practitioners, and anyone interested in promoting epistemic justice with and for young people.